Coal-based sulfur hybrid sorbent for removal of Hg0 from flue gas. Part 1. High inorganic sulfur coal. (15th March 2022) - Huo, Qihuang; Wang, Yahui; Chen, Huijun; Feng, Yu; Han, Lina; Xie, Wei; Wang, Jiancheng; Bao, Weiren; Chang, Liping; Xie, Kechang
Graphical abstract: Highlights: A novel mercury sorbent was prepared from a high inorganic sulfur coal (HISC). The sorbent shows high Hg 0 removal efficiency under complex gas conditions. The active sulfur in the sorbent reacts with Hg 0 to form stable HgS. Abstract: A novel sulfur hybrid mercury sorbent was successfully prepared by chemically activating high inorganic sulfur coal using potassium hydroxide (KOH). The optimal conditions for preparing the sorbent are at 800 °C with the ratio of KOH/coal at 2:4 by mass. The prepared sorbent, named ZY-2:4-800, containing 0.92% sulfur with a high specific surface area of 353 m 2 ·g −1, has a wide temperature range for mercury removal. Between 60 and 180 °C, the Hg 0 removal efficiencies of this sorbent keep above 95% within 2 hr under N2 +O2 +NO+SO2 +H2 O. This is because that O2 can slightly improve the mercury removal ability of the sorbent, and it shows great resistance to acid gas (NO and SO2 ) and H2 O. The calculated Hg 0 adsorption capacity of ZY-2:4-800 is 214.7 μg·g −1, which is much higher than that of activated carbon sorbent (ACs) reported in the literature. Based on XPS and Hg-TPDD analysis, it is revealed that the iron sulfide compounds in coal can be converted into active sites as S 0, S2 2–, and C-S during the preparation of the sorbents, and Hg interacts with these active sites and forms β-HgS (metacinnabar). The excellent mercury removal performance and the low cost indicate that the as-prepared sorbent from the blend of the high inorganic-sulfur coal and KOH is a promising sorbent for mercury removal from flue gas. It is expected that this method could be applicable in converting other high-inorganic sulfur coals into efficient mercury sorbents.